2015
DOI: 10.1017/s0016756815000771
|View full text |Cite
|
Sign up to set email alerts
|

Petrography and geochemistry of the siliciclastic Araba Formation (Cambrian), east Sinai, Egypt: implications for provenance, tectonic setting and source weathering

Abstract: Combined petrographic and geochemical methods are utilized to investigate the provenance, tectonic setting, palaeo-weathering and climatic conditions of the Cambrian Araba clastic sediments of NE Egypt. The ~ 60 m thick Araba Formation consists predominantly of sandstone and mudstone interbedded with conglomerate. Petrographically the Araba sandstones are mostly sub-mature and classified as subarkoses with an average framework composition of Q80F14L6. The framework components are dominated by monocrystalline q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 57 publications
0
31
0
Order By: Relevance
“…The major‐element‐based discrimination diagrams of Bhatia () and Roser and Korsch () for clastic sediments have been traditionally used in various studies to identify the tectonic setting of unknown basins (e.g., Tawfik et al, , ). However, numerous studies have confirmed that the results obtained from such diagrams were inconsistent with the general geology of the investigated areas (Khan & Khan, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The major‐element‐based discrimination diagrams of Bhatia () and Roser and Korsch () for clastic sediments have been traditionally used in various studies to identify the tectonic setting of unknown basins (e.g., Tawfik et al, , ). However, numerous studies have confirmed that the results obtained from such diagrams were inconsistent with the general geology of the investigated areas (Khan & Khan, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, on the basis of the geochemical composition of Miocene to Recent sediments, Verma and Armstrong‐Altrin () proposed two discriminant‐function‐based major‐element diagrams for the tectonic discrimination of siliciclastic sediments from three main tectonic settings; island or continental arc, continental rift, and collision. In fact, these discrimination diagrams were successfully used in recent studies to discriminate the tectonic setting of a source region based on the geochemistry of clastic sediments (e.g., Armstrong‐Altrin & Machain‐Castillo, ; Guadagnin et al, ; Nagarajan et al, ; Tawfik et al, ; Zaid, , , ). On these high silica and low silica multidimensional diagrams, most studied samples plot within the collision field (Figure a,b).…”
Section: Discussionmentioning
confidence: 99%
“…Three different tectonic settings can be classified on these diagrams including island arc, rift, and collision. These diagrams had been successfully applied to discriminate tectonic setting of clastic sediments in recent studies (Armstrong‐Altrin, Nagarajan, et al, ; Tawfik et al, ; Verma & Armstrong‐Altrin, ; Zaid, ). In the present study, the (SiO 2 ) adj contents of the Quemoco sandstones vary from 55.6% to 68.0% (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have certified that the chemical components of terrigenous sediments are closely connected with the tectonic setting of source area (Bhatia & Crook, ; Fatima & Khan, ; Moosavirad, Janardhana, Sethumadhav, Moghadam, & Shankara, ; Sun, Gui, & Chen, ), which have been extensively applied to analyse the provenance (Madhavaraju, ; Sun et al, ; Tawfik, Ghandour, Maejima, Armstrong‐Altrin, & Abdel‐Hameed, ; Zaid, ) and constrain the tectonic setting (Armstrong‐Altrin et al, ; Armstrong‐Altrin, Nagarajan, Balaram, & Natalhy‐Pineda, ; Moosavirad et al, ; Tao, Sun, Wang, Yang, & Jiang, ) of sedimentary basins in the past 20 years. To deduce the tectonic setting, previous studies are continuously using the traditional tectonic identification diagrams put forwarded by Bhatia () Fe 2 O 3 T + MgO vs. TiO 2 , Fe 2 O 3 T + MgO vs. Al 2 O 3 /SiO 2 , Fe 2 O 3 T + MgO vs. K 2 O/Na 2 O) and Bhatia and Crook () La–Th–Sc, Th–Co–Zr/10, Th–Sc–Zr/10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation